Pengaruh Profitabilitas Terhadap Harga Saham dengan Ukuran Perusahaan Sebagai Variabel Moderating Pada Perusahaan Sektor Food And Beverage Di Bursa Efek Indonesia 2020-2022 - Purba, Melfrianti Romauli; Sitorus, Paskah Ria; Andari, Ayu; angelia, nia; Nababan, Tiorika (JEBIM Prima, 2024)
The Indonesian capital market consists of several sectors, including the food and beverage sector. Until now, there has been no research focused on manufacturing companies in that sector. The method employed in this study is associative quantitative research. Data collection is conducted by accessing financial statement documents from www.idx.co.id for the period 2020-2022. For data analysis, the researcher uses methods such as multiple linear regression, coefficient of determination, t-test, and F-test. The research sample comprises 31 companies with data spanning 3 years, selected through purposive sampling. The findings indicate that the profitability ratio has a significant impact on stock prices, with company size acting as a moderator that moderates the influence of profitability on stock prices in Food and Beverage Sector Manufacturing Companies listed on the IDX in 2020-2022, amounting to 14.2%. The moderator variable can strengthen the impact of profitability variables on stock prices.